PENDAMPINGAN MANAJEMEN USAHA PADA UKM SEPATU BERSIH DI MALANG - Siti Zubaidah; Masiyah Kholmi (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat, 2020)
This service was carried out in the clean shoe business group. The purpose of this service is to form / develop a group of people as prospective entrepreneurs who are economically independent with a specific target to be achieved is to provide assistance in business management, especially in the bookkeeping and sales system of UKM Clean Shoes in Malang. The partner in this service is UKM "Clean Shoes". Clean shoes is a brand of premium shoes treatment service provider that has been engaged in Malang since May 2014. The services offered include fast clean, deep clean, unionization, women care, recolour upper, recolour midsole, reglue, shoes sanitizer, customeshoe , and pick up delivery. The main problem of SMEs and agreed to be resolved first is that there is no good bookkeeping and sales system, The method used in solving partner problems is providing assistance and tutorials on bookkeeping and sales systems.